Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Karyawan Melalui Komitmen Organisasional Sebagai Variabel Intervening Pada Kantor Balai Kota - Ainul Qodri; Dian Rista; Chintya Ones Charli; Lara Sulmi Riva; Wulandari Oktavia (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to determine the influence of the work environment and workload on employee performance through organizational commitment as an intervening variable at the Solok city hall office. This research includes causal associative research using a quantitative approach. The results of this research show that the work environment has a significant influence on employee performance, work workload has an influence on employee performance, work environment and workload have a positive and significant effect on employee performance.